2011
DOI: 10.1080/07317115.2011.573407
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Elder Mistreatment and Its Link to Help-Seeking Intention: A Comparison of Elderly Korean and Korean American Immigrants

Abstract: The study examined perceptions of elder mistreatment (EM) and help-seeking intentions in two older Korean cohorts-residents in Korea ( n = 124) and Korean immigrants ( n = 124) in the United States, recruited using a quota sampling strategy. A mixed method survey utilized four hypothetical scenarios of physical, financial, and psychological abuse and neglect. A majority of participants perceived physical, financial, and psychological abuse scenarios as EM but not the neglect scenario. Multivariate analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…This result strongly implies that help-seeking might be guided by a complex process involving both the interplay of cultural and social factors and differences in gender. Korean elders' low intention to seek help is corroborated by previous studies that also examined various ethnic elderly groups' help-seeking behavior in the face of EM (Lee et al, 2011;Moon, Tomita, & Jung-Kamei, 2001;Moon & Williams, 1993; see also Lee, Kaplan, & Perez-Stable, this issue). In these studies, Korean elderly immigrants were consistently found to have unfavorable attitudes toward reporting abuse or receiving outside intervention.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result strongly implies that help-seeking might be guided by a complex process involving both the interplay of cultural and social factors and differences in gender. Korean elders' low intention to seek help is corroborated by previous studies that also examined various ethnic elderly groups' help-seeking behavior in the face of EM (Lee et al, 2011;Moon, Tomita, & Jung-Kamei, 2001;Moon & Williams, 1993; see also Lee, Kaplan, & Perez-Stable, this issue). In these studies, Korean elderly immigrants were consistently found to have unfavorable attitudes toward reporting abuse or receiving outside intervention.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, for the Korea-based cohort, perception was found to be the only significant factor associated with help-seeking intention. This significant link of perception with help-seeking intention has been supported by prior studies in EM research among elderly Korean immigrants (Lee et al, 2011;Moon & Williams, 1993).…”
Section: Discussionmentioning
confidence: 61%
“…In addition to differences in reporting based upon professional identity Rosenblatt et al, 1996), research involving vignettes has revealed that groups differ in what they define as abusive (see, e.g., Lee et al, 2011;Moon, 2000). As the population of older adults becomes increasingly diverse, research on the definitions of mistreatment, and perceptions (and misperceptions) about APS intervention will continue to be necessary in order to improve response to the needs of abused and neglected older adults.…”
Section: Reporting Abuse and Neglectmentioning
confidence: 97%
“…The bulk of research attention on this topicwas devoted to two groups, Asian American elders (Dong, 2014; Le, 1998; Lee & Shin, 2010; Lee et al, 2011; Lee, Kaplan, & Perez-Stable, 2014; Moon et al, 1998; Moon, Tomita, & Jung-Kamei, 2002; Pablo & Braun, 1998; Yan & Tang, 2001) and African Americans (Benton, 1999; Hudson & Carlson, 1999; Shellman, 2004; Tauriac & Scruggs, 2006). Only a few empirically based research articles on the conceptualization of elder mistreatment had a primary emphasis on Latino (Franco, Gray, Gregware, & Meyer, 2000; Mitchell, Festa, Francis, Juarez, & Lamb, 1999; Paulino, 1998) or American Indian/Alaska Native elders (Hudson, Armachain, Beasley, & Carlson, 1998; Jervis, 2014).…”
Section: Elder Mistreatment and Underserved Groups: What Is Knownmentioning
confidence: 99%